The Optimization of Children’s Autism Psychosocial Service on Online School Learning - Nasith, Ali; Bashith, Abdul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The study aimed to describe and analyze APA psychosocial conditions during online schooling and learning strategies at SLBB. This research was conducted at SLBB & Autis TPA Jember by monitoring the psychosocial situation of autistic children while studying at home to find out what programs or services can support children’s psychosocial support even though it is implemented online. This type of research uses descriptive with a qualitative approach—determination of location using the purposive area. The informant determination technique uses purposive sampling. The data collection techniques were applied with observations, interviews, and documentation. Data analysis techniques include data collection, reduction, presentation, conclusion, and verification. Data validity techniques use source triangulation and methods. The study results show a tendency for psychosocial disorders to occur in children while studying online, but it can be overcome with psychosocial services. This disorder affects the behavioral and emotional conditions of children who are increasingly out of control at home. Therefore, to overcome this difficulty, the teacher provides services that can improve psychosocial disorders in autistic students. The services provided include educational suggestions not to consume foods that cause excessive activity, education for independent living so that students can be trusted not to violate rules, and wearing soft clothes. The function of these services is to control emotions by selecting the right teacher so that students want to obey positive commands that are good for them, and students also consume herbal drinks so that emotions can be controlled more. Then the psychosocial services strategies that are used online is to overcome difficulties experienced by students while at home, including selecting or changing homework assignments that can develop students’ interest and talents, home visit, and valuable educational content on TV so that children’s development continues to run optimally and is ready to interact out on time.